(untitled) (Ustozlar uchun, 2025)
Effective lesson planning is paramount for all educators, but it takes on particular significance when teaching English Language Learners (ELLs). This paper examines the critical components and pedagogical principles involved in designing lesson plans that cater to the unique linguistic and academic needs of ELLs across diverse proficiency levels and cultural backgrounds. We argue that successful ELL-focused lesson plans move beyond generic templates to integrate explicit language objectives alongside content objectives, scaffold learning through deliberate strategies, emphasize meaningful interaction, and incorporate ongoing formative assessment. By detailing practical strategies for differentiation, vocabulary pre-teaching, visual support, and authentic communication, this article provides educators with a comprehensive framework to create engaging, accessible, and academically rigorous learning experiences that empower ELLs to achieve both language proficiency and content mastery.